Einstein’s Dream - Parker, Barry R. author. aut Link
IX, 287 p. 30 illus.
Keywords: Thirty years ago Albert Einstein died, his dream of a theory that would unify the universe unfulfilled. He spent the last decades of his life searching for such a theory-a theory that would explain everything from elementary particles and their interac tions to the overall structure of the universe. But he failed, not because he didn't try hard enough, but because the attempt was ahead of its time. When Einstein worked on the problem liter ally nothing was known about black holes, white holes, sin gularities, the Big Bang explosion and the early universe, quarks, gauge invariance, and weak and strong nuclear forces. Today we know that all these things are important in relation to a unified theory, and that they must be incorporated in and explained by such a theory. Thus, in a sense, our problem is much more complex today than it was in Einstein's day. But scientists have persevered and as a result we are now tan talizingly close to achieving this long-sought goal. Important breakthroughs have been made. In this book we will look at these breakthroughs and at recent unified theories-theories that go by the names supergravity, superstrings, GUTs, and twistor theory. In order to understand the problem, however, we must begin at the beginning.